Status of Forest Biomass and Carbon Stock Assessment in South Asia - Sivaram, M.; Sandeep, S.; Matieu, H. (Indian Forester, 2016)
In this paper, the status of forest biomass and carbon stock assessment in South Asia has been reviewed based on the reports of Forest Resource Assessment (FRA) -2010 published by FAO. The quality of the data reported to FAO is medium to high. The countries heavily depend on growing stock volume from National Forest Inventory reports for biomass and carbon estimation. While the National Forest Inventory is being carried out in India at regular intervals, other countries are attempting or in the process of undertaking periodic forest inventory. Besides updating the existing database of volume and biomass allometric equations, the regional/country specific biomass and carbon conversion factors are required to improve the present biomass and carbon estimates.